Analisis Tarif Transportasi Publik: Studi Kasus Bus Trans Metro Dewata Bali Dengan Memperhitungkan Biaya Operasi Kendaraan, Ability To Pay, dan Willingness To Pay - Dwiputranti, Made Irma (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
One of the transportation tools used in Bali is a bus fleet called Trans Metro Dewata (TMD) Bali. TMD Bali bus is one of the public transportation that has various destinations, where one of themajors is in Corridor 1, Central Parking Kuta-Terminal Pesiapan. TMD Bali bus corridor 1 has aroute of Central Parking Kuta-Terminal Tegal- Terminal Mengwi- Terminal Pesiapan. Trans MetroDewata Bus Public Transportation is a link between the Kuta Central Parking area - TerminalPesiapan which is an area of the Tabanan City area that connects the Kuta tourist area andthetrade center which is one of the centers of tourism activities, and vice versa. Currently, thenumber of buses operating is a total of 105 buses of which 95 buses are used for operationalpurposes while the rest are for reserves, with a fare of IDR 4400 for the standard fare fromKutaCentral Parking Lot - Terminal Pesiapan. Operational activities of the Bali Trans Metro DewataBuspublic transport company began to develop well because previously the TMD Bali bus farewasfree, but since October 31, 2022 began to be charged. The tariff is in return for the servicesreceived by users to cover all vehicle operating costs and a decent profit for the operator. Formulation of Bus public transport tariffs in addition to paying attention to the operating costs of the vehicle but also must pay attention to the purchasing power or ability to pay of service users(Ability To Pay) as well as the perception of users of public transport services Bus Corridor 1Central Parking Kuta-Terminal Pesiapan (Willingnes To Pay).The results showed that the current tariff of public transportation bus Sentral Parking Kuta-Terminal Pesiapan which is Rp 4,400.00isnot in accordance with the Ability to Pay and Willingness to Pay passengers of publictransportation bus Sentral Parking Kuta-Terminal Pesiapan. The tariff that is in accordancewiththe Ability to Pay and Willingness to Pay passengers of public transportation bus Sentral Parkingkuta-Terminal Pesiapan based on the results of the calculation is Rp 4,000.00.